The Influence of Product Quality and Prices on Government Brand Products (Foodstation) on Purchasing Decisions at Jakmart Pasar Jaya Cikini - Pasaribu, Veta Lidya Delima; Mohamad Aldo Husein (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the influence of product quality and price on FS brand government products on purchasing decisions at Jakmart Pasar Jaya Cikini.